Case report: Effectiveness of sirolimus in treating partial DiGeorge Syndrome with Autoimmune Lymphoproliferative Syndrome (ALPS)-like features - Gu, Hao; Mou, Wenjun; Chen, Zhenping; Xie, Xingjuan; Yao, Jiafeng; Zhang, Rui; Wu, Runhui; Gui, Jingang (Frontiers in Pediatrics, 2023)
Background: DiGeorge syndrome (DGS) is a common copy-number variant disorders caused by a microdeletion in chromosome 22q11.2. Hematologic autoimmunity is rare and refractory in DGS with a poor prognosis. Due to different mechanism of the hematologic autoimmunity manifestations, an effective and standard treatment for immune cytopenia has not been established for DGS patients. Case Description: A 10year-old boy presented initially with ventricular septal defect at 7 months of age. At the age of 30 months, thrombocytopenia was found and progressed to chronic refractory ITP (CRITP) till lymphoproliferative symptoms was noted at 6years old. At 7 years of age, despite CRITP the patient developed multilineage immune-related cytopenia with anemia and neutropenia. First-line treatment of immune thrombocytopenia like prednisone and intravenous immune globulin (IVIG) had no apparent effect on the symptoms. Whole-exome sequencing revealed the presence of a heterozygous copy number deletion on the 22q11.21 in the patient. Decreased proportion of naïve T cells and elevated double negative T cell (DNT) were found by laboratory test. Elevated DNT and lymphoproliferative symptoms are associated with an increased activation of mammalian target of rapamycin (mTOR) pathway involved in the Pathogenesis of autoimmune lymphoproliferative syndrome (ALPS). Treatment with sirolimus, a mTOR inhibitor, was initiated with spotlight of elevated DNT and lymphoproliferative syndrome. Soon after initiation of treatment with sirolimus, cytopenia and lymphoproliferative symptoms showed a complete response and resulted in improved patient growth and quality of life. Conclusions: This case represents the first detailed report of aiming DNT successful sirolimus therapy for refractory multi-linage cytopenias of DGS.